ANALISIS DAN PERBANDINGAN SEKTOR UNGGULAN DI KOTA MAKASSAR DAN KOTA PAREPARE DAN PERANNYA DALAM MENUNJANG PEREKONOMIAN PADA PROVINSI SULAWESI SELATAN - Gaby, Baiq Regina; Hasbi, Hasbi; Sufri, Muchlis; Alamsyah, Alamsyah (Economos : Jurnal Ekonomi dan Bisnis, 2021)
Economic activity is an activity carried out by humans to obtain certain goods or services according to their needs. This activity is expected to be able to achieve prosperity in life. The aims of conducting this research are; 1) To know the leading sectors in Makassar and Parepare; 2) To find out the comparison of leading sectors in Makassar and Parepare, and 3) To find out and analyze the role of the leading sector in supporting the economy in their respective regions. The data used in this research was secondary, namely, data on the gross regional domestic product, distribution, and growth rate according to business fields in Makassar and Parepare for the period 2011-2020, Location Quotient, Dynamic Location Quotient, and Growth Ratio Models combined in the Analysis table Overlays. The results of the research indicated that there were 2 sectors based on the analysis overlays scored more than 1 on each indicator in Makassar, namely construction and health services, while in Parepare there were 5 sectors namely electricity and gas procurement, accommodation, and food and drink provision, financial and insurance services, real estate, and health services. Based on the results, these sectors are the main development priorities that are superior and prospective sectors and have good growth in their region and province.Â